Transcriptome study on the effect of leaf-fruit ratio on molecular regulation mechanism of Camellia oleifera - Xiaoyan Zhang; Hui Zhang; Xiuzhong Wu; Zhanying Gu; Lingli Wu; Xiaofeng Tan; Ze Li (BMC Plant Biology)
Abstract Background Camellia oleifera Abel. is one of the four major woody oil species whose seeds produce high-grade edible oil. In recent years, the planting area of Camellia oleifera is increasing in China. However, in the process of cultivation, due to the high fruit load, the Camellia oleifera tree has small fruit and poor quality. In previous studies, we explored the optimal leaf-fruit ratio. In this study, the changes of molecular regulation mechanism of Camellia oleifera under different leaf-fruit ratios were revealed by combining physiological indexes with transcriptome data. Result The physiological results showed that the content of MDA and starch in leaves increased significantly with the decrease in the leaf-to-fruit ratio. The results of transcriptome showed that there was a close relationship between leaf-fruit ratio and phenylpropanoid biosynthesis pathway. With the decrease of leaf-fruit ratio, the expression of genes related to lignin and flavonoid biosynthesis increased significantly, which promoted the synthesis of lignin and flavonoid. Conclusions Combining physiological indicators and transcriptomics, we demonstrated that leaf-fruit ratio can significantly affect the normal growth of plants. When the fruit load is too high, the fruit as a ‘sink’ will consume a large amount of nutrients in the plant body and promote the biosynthesis of lignin and flavonoids in the body. The results provide a more reliable scientific basis for the study of cultivation and management of Camellia oleifera.